THE CONCEPTUAL OF SUSTAINABLE SETTLEMENT WITH PARTICIPATORY APPROACH - Fuad Zubaidi (Journal of Architecture&ENVIRONMENT, 2012)
Sustainable development of settlement is an attempt to improve the quality of human life from the aspect of environmental sustainability, social, or economic, which is done to integrate and harmonize three aspects. Donggala Kodi is one of the areas included in the administrative boundaries of the Palu city which a with fairly steep slope topography and height of 200m. Under these conditions, in principle, to make into one of the proneness. Development of settlement areas by utilizing its asset base, need to specify the form of the space requirements, related social, economic and environmental. This is to achieve sustainable development, as well as how to address the imbalance that exists. Participatory approach with the involvement of the community in order to draw up conceptual sustainable settlements is one effective approach to solve the problem. This paper discusses how the preparation of conceptual framework of sustainable settlements with community participation approach. The result of the discussion related to the formulation of the concept of residential development on the socio-economic empowerment of the community, and using the environment-based community.